First, we can manipulate the second equation to solve for x:
x + 3y = -24
x = -24 - 3y
Now we can substitute this expression for x into the first equation:
9(-24 - 3y) - 7y = 22
-216 - 27y - 7y = 22
-216 - 34y = 22
-34y = 238
y = -7
Now that we have found the value of y, we can substitute it back into the second equation to solve for x:
x + 3(-7) = -24
x - 21 = -24
x = -3
Therefore, the solution to the system of equations is (x, y) = (-3, -7).
Therefore, the correct answer is: (−3,−7).
Use the elimination method to solve the follow system of equations.
9x−7y=22
x+3y=−24
This question requires you to show your work.
(1 point)
Responses
(0,−8)
(4, 2)
(−3,−7)
(3,−9)
1 answer